Formulation & Evaluation Rosella Suspension (Hibiscus sabdariffa L.) as Immunomodulator with Variation of Carboxymethylcellulose Sodium Concentration (Universitas Muhammadiyah Yogyakarta, 2025)
Rosella flower (Hibiscus sabdariffa L.) has proven in previous studies through clinical trials and preclinical trials to be safe as an immunostimulant. The purpose of this study was to determine the stability of suspension preparation by varying the concentration of CMC Sodium as a suspending agent. The suspension preparations into 4 formulas, Formula 0 (without CMC Sodium), Formula 1 (CMC Sodium 1.5%), Formula 2 (CMC Sodium 1.75%), Formula 3 (CMC Sodium 2%). The results in the organoleptical test showed that the dosage form F0 was liquid, F1 and F2 were slightly thick liquid, F3 was thick. Density test results in F0 1.09g/mL, F1, F2 and F3 1.10g/mL. Viscosity test on F0 20.8 cps, F1 128.6 cps, F2 268.6 cps and F3 475.6 cps. The pH test of all formulas is in the acidic range. Sedimentation test F0 = 1, F1 and F2 = 0.97 and F3 = 0.99 or close to 1. Redispersion time test of all preparations <30 seconds. The good formula based on the evaluation of suspension rosellaa preparations, namely F1 and F2 with Na CMC concentrations of 1.5% and 1.75%.